Sustainability-oriented innovation through shaping the ecosystem; a case of an e-bus industry in Indonesia - Muhammad Taufiq Amir; Bulan Prabawani (Cogent Business & Management, 2023)
Sustainability orientation is increasingly becoming a focus in companies' top management. In addition to social, environmental, and economic impacts, a sustainability-based strategy can be a source of excellence for the company in the future. Using the Network for Business Sustainability model as a lens, this study examines how companies are involved in the challenge of forming an ecosystem that is still not mature when developing the electric bus business. It includes how companies change their business orientation, identify and collaborate with stakeholders, and encourage the acceleration of regulatory existence. The company and new business' top management were interviewed to understand the company's orientation as part of a group of companies. A total of six interviews were conducted for this purpose. The factor of reconceptualizing the business's purpose and influencing the ecosystem through strategy, linkages, and learning was explored as the determining factor. Flexibility in business models, influential partners in global supply chains, and good relations with government agencies were also crucial factors. This study contributes to research on sustainability-oriented innovation, and corporate entrepreneurship. This study provides a comprehensive and general framework for sustainability-oriented innovation, highlighting the guiding principles of any ecosystem approach to innovation management.
Keywords: 650; business development strategy; electric bus; EV ecosystem; Sustainability oriented innovation; venture creation